Activity 13 Graduate vacancy application exercise : tutor - UK Physical Sciences Centre; University of Hull; Grice, Della (The University of Hull)
This resource is the tutor guide for student activity 13 as part of a broader resource called the Employability Resource Pack. There are also a series of sample vacancies in a separate resource which can be used to practice with.